PENGARUH RASIO KEUANGAN TERHADAP PENCAPAIAN LABA PERUSAHAAN KELOMPOK INDUSTRI MAKANAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Akhmad Sodikin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The aims of this research are to know influence of finacial ratios which consisted of Current ratio, Debt equity ratio, Leverage ratio, Inventory turn over, and total assets turn over to return on equity simultanously and to know influence of finacial ratios which consisted of Current ratio, Debt equity ratio, Leverage ratio, Inventory turn over, and total assets turn over to return on equity partially. Data was analyzed used fixed effect model. Data which collected for 3 years from 2011 until 2013 comes 8 firms in food industries listed in Indonesian Stock Exchange (IDX). Based on data analyzed was known that finacial ratios which consisted of Current ratio, Debt equity ratio, Leverage ratio, Inventory turn over, and total assets turn over to didn’t influence to return on equity simultanously and finacial ratios which consisted of Current ratio, Leverage ratio, Inventory turn over, and total assets turn over didn’t inluence to return on equity partially but debt equity ratio influence significantly to return on equity.